The Shariah-Compliant Risk Factor and Distress Risk: Evidence from the U.S. Stocks - Olfa Ben Mdalla; Olfa Benouda (Bank Indonesia, 2026)
This paper tests the Shariah-compliant-augmented three-factor model (TFM) in the U.S. stock market from July 2005 to June 2024. In particular, we investigate whether the Shariah Compliant (SC) risk factor, measured as the difference in returns between the portfolio of non-Shariah-compliant (NSC) firms and that of SC firms, constitutes a systematic source of risk able to explain financial distress. We find that the SC risk factor is a major determining factor in pricing of stock portfolios classified by size, book-to-market and Shariah compliance, along with those of distressed and non-distressed firms. Additionally, we point out that the SC risk factor explains the cross-section of stock returns even when other financial distress risk factors are considered, suggesting that it contains significant distress-related information. Finally, we show that this risk factor is significantly related to innovations in term spread, which is consistent with Merton’s ICAPM explanation. Overall, the findings indicate that the SC factor represents a systematic, undiversifiable distress risk factor. These results have important implications for asset management using SC stocks, supporting an SC-augmented TFM to fairly value assets and suggesting that SC investment may provide protection against financial distress.